Outbreak of betanodavirus infection in cage-cultured Asian seabass (Lates calcarifer Bloch): A case study in Odisha - K.P. Jithendran; P.K. Sahoo; C.P. Binesh; B.R. Mohanty (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Viral encephalopathy and retinopathy (VER) or viral nervous necrosis (VNN) is an infectious neuropathological disease affecting more than 120 fish species. Although VER affects mainly marine fish , the disease has also been detected in certain species reared in low  saline and freshwater environments. In the present study, a case of betanodavirus associated massive mortality was investigated in juvenile seabass Latescalcarifer, maintained in cage culture facilities in brackishwater pond in Odisha(India).The affected fish showed clinical signs typical of betanodavirus infection around 70 days post hatch (dph), resulting sudden mass mortality in all the cages affecting almost 100% of the population. Histopathology revealed massive necrosis of tubules in kidney and mild vacuolation of the nervous system, suggesting an infection by betanodavirus.The presence of virus was detected and confirmed by nested RT-PCR assay and sequence analysis of PCR product. Sequencing of the PCR product indicated sequence homology with red-spotted grouper nervous necrosis virus(RGNNV) type.However , the reservoir of the virus leading to the outbreak remains unidentified but suspects the infected fry as source. This is the first report of mortality associated with natural infection of betanodavirus infection in inland cage farming facilities in India.